PERAN PEREMPUAN DALAM MEMBANGUN KERUKUNAN UMAT BERAGAMA : STUDI KOMPARATIF INDONESIA DAN MALAYSIA - Daimah Daimah (EL-TARBAWI, 2018)
Empowering women in various dimensions of religious social life has received global attention among women observers and observers of development issues. In building religious harmony, women can play a role in two sectors, namely the role of women in the family and the role of women in social life. In the family, the role of women as a wife and at the same time as a mother becomes an example in acting in the family. Likewise with the role of women in social life, women are able to contribute to the avodication of peace in creating religious harmony. Keywords: The Role of Women, Harmony of Embrace The Religion, Indonesia, Malaysia